Technical Error Factors On Panoramic Radiographic Examination At The Radiology Installation Of Unjani Dental and Mouth Hospital - Asriningrum, Surdiyah; Sudrajat, Ismayanti; Meliawati, Mely (Rescollacom (Research Collaborations Community), 2023)
Panoramic is a three-dimensional curved zone where anatomical structures are well defined on panoramic radiography. Panoramic radiography includes a detailed anatomy of the jaw complex with some superimpositions and distortions that can be exacerbated by technical errors in image acquisition as well as many extra-jaw anatomical structures that are able to give clear description to interpretate. Therefore, in obtaining a panoramic radiograph it is necessary to obtain the desired structure with high quality and minimal distortion. Errors that often occur in producing good panoramic radiographs are technical errors or when positioning the patient and during the panoramic examination. The purpose of this study was to determine the main factors causing the errors so that technician can produce good quality radiographs, take into account patient placement at the time of examination, perform film processing, and handle general film procedures. The research method used was a quantitative method with a descriptive observational approach. The number of samples was 64 radiographs, which are adult patients over 18 years old with the use of exposure factors in the range of 60kV, 10mA and 16.4s. All radiographs were taken by qualified radiographers with more than 5 years of experience. The radiographs were viewed and observed without any modification on a computed radiography monitor screen. Radiographic results will be evaluated by experienced technician who have worked more than 5 years. Evaluation is obtained by analyzing the data descriptively in the form of assessment of the percentage of rejection of panoramic radiographs to make conclusions. Out of the 2418 panoramic radiographs viewed, 2354 (97%) radiographs had no errors while 64 (3%) radiographs showed one or more positioning error. The most common positioning error observed in the radiographs was failuer to position chin tipped high (56,02%). Whereas the least common error recorded were movement and apron shadow (1.15%).